Adults Without Advocates and the Unrepresented: A Narrative Review of Terminology and Settings - Rachel Brenner MD; Linda Cole MS; Gail L. Towsley PhD, NHA, FGSA; Timothy W. Farrell MD, AGSF (Gerontology and Geriatric Medicine, 2023)
Socially isolated adults, including those with and without the ability to make medical decisions, are encountered in clinical practice and are at risk for adverse health outcomes. Consensus is lacking on appropriate terminology to describe subpopulations of these patients. In addition, little is known about the settings in which they present. These gaps prevent clinicians and policymakers from identifying and understanding these populations and deploying appropriate resources to meet their complex needs. We conducted a narrative review of literature on socially isolated adults aged 50 and older to assess and integrate the available evidence regarding the terminology used to describe unrepresented patients and adults without advocates to inform consensus on terminology. We also identified the settings in which unrepresented patients and adults without advocates are described in the literature, including both within and outside health care settings. Our results indicate that there is heterogeneity and inconsistency in the terminology used to describe socially isolated adults, as well as heterogeneity in the settings in which they are identified in the literature. Our findings suggest that future work should include achieving consensus on terminology and integrating proactive interdisciplinary interventions across health systems and communities to prevent adults without advocates from becoming unrepresented.